Kondisi Rumah Tidak Layak Huni (RTLH) di Indonesia - Lumban Tobing, Putri I; Gede Karma Wisana, I Dewa (UI Scholars Hub, 2024)
Urbanization in Indonesia is increasing population growth and demand for habitable housing, presenting challenges. This study assesses uninhabitable houses (RTLH) across regions and provinces, examining their relationship with drinking water, sanitation access, and regional and macroeconomic factors. Despite progress, significant gaps in access to improved water and sanitation persist. Using data from the Central Statistics Agency, findings show a slowed decline in RTLH from 2019 to 2021, with an increase in 2022, highlighting uneven development. The study also finds that higher education levels correlate with lower RTLH rates, while a larger informal labor force is linked to higher RTLH.